تحليل هوالك التشييد السورية وصياغة نموذج لتقليل هوالك حديد التسليح - جراد فايز (Latakia University Journal -Engineering Sciences Series, 2017)
تؤثر الهوالك الناتجة عن عمليات التشييد في المشروع بحيث تضيف قيم مالية للمشروع دون أن تؤدي إلى أي تحسين فيه، ودون أن تؤدي الى الإرتقاء بمقدرات المشروع الوظيفية، كما تؤدي إلى زيادة الكميات المطلوبة وبالتالي زيادة كلفة المشروع وتراكم النفايات الصلبة الضارة بالبيئة. سوف نناقش في هذا البحث أهم العوامل المؤثرة على زيادة الهوالك في مشاريع التشييد السورية من خلال تحديد أهم الأسباب التي تؤدي الى زيادة الهوالك في المواد كذلك تحديد أهم الاسباب التي تؤدي الى زيادة الهوالك والمرتبطة بالتصميم أو التخزين أو الاشراف. سيتم ترتيب هذه العوامل لتحديد أكثرها تأثيراً على المشروع. في نهاية البحث ستتم صياغة نموذج رياضي لأمثلة قص قضبان حديد التسليح في المشروع واستخدام برنامج Lindo لحل هذا النموذج فقد تبين من خلال الدراسة أن نسبة كبيرة من هوالك حديد التسليح ناتجة عن عشوائية القص للقضبان. Waste resulting from construction operations affect the project, so that it adds financial values of the project, without leading to any improvement in it,or to improve the functional capabilities of the project, and lead to increased quantities required, thereby increasing the cost of the project and the accumulation of environmentally harmful solid waste. In this research, We will discuss the most important factors affecting the increase waste in the Syrian construction projects by identifying the most important causess that lead to an increase in waste materials, as well as identify the most important causes that lead to increased waste associated with design, storage or supervision. These factors will be arranged to determine the most effective on the project. At the end of the research we will formulated mathematical model to Optimize cutting of reinforced steel bars and Lindo program will be used to solve this model. It has been shown by the study that a large proportion of waste is resulting from random cutting bars.